Equilibrium Reconstruction and Integration of EFIT with Diagnoses in J-TEXT Tokamak - 高海龙 徐涛 张帆 简翔 张晓卿 杨州军 高丽 江中和 庄革 (等离子体科学与技术：英文版, 2016)
The EFIT program is integrated with the high resolution laser polarimeter interferometer system(POLARIS), the soft X-ray imaging diagnostic system(SXR) and the electron cyclotron emission radiometer(ECE) in the J-TEXT tokamak. Then some internal information about Faraday angle and the position of safety factor q=1 can be obtained as a constraint to EFIT. The modified EFIT code is used to calculate the internal parameters such as flux function, safety factor q, pressure and current density.